Combined onabotulinumtoxinA/atogepant treatment blocks activation/sensitization of high-threshold and wide-dynamic range neurons. (January 2021) - Melo-Carrillo, Agustin; Strassman, Andrew M; Schain, Aaron J; Adams, Aubrey Manack; Brin, Mitchell F; Burstein, Rami
Background: OnabotulinumtoxinA and agents that block calcitonin gene‒receptor peptide action have both been found to have anti-migraine effects, but they inhibit different populations of meningeal nociceptors. We therefore tested the effects of combined treatment with onabotulinumtoxinA and the calcitonin gene‒receptor peptide antagonist atogepant on activation/sensitization of trigeminovascular neurons by cortical spreading depression. Material and methods: Single-unit recordings were obtained of high-threshold and wide-dynamic-range neurons in the spinal trigeminal nucleus, and cortical spreading depression was then induced in anesthetized rats that had received scalp injections of onabotulinumtoxinA 7 days earlier and intravenous atogepant infusion 1 h earlier. The control group received scalp saline injections and intravenous vehicle infusion. Results: OnabotulinumtoxinA/atogepant pretreatment prevented cortical spreading depression-induced activation and sensitization in both populations (control: Activation in 80% of high-threshold and 70% of wide-dynamic-range neurons, sensitization in 80% of high-threshold and 60% of wide-dynamic-range neurons; treatment: activation in 10% of high-threshold and 0% of wide-dynamic-range neurons, sensitization in 0% of high-threshold and 5% of wide-dynamic-range neurons). Discussion: We propose that the robust inhibition of high-threshold and wide-dynamic-range neurons by the combination treatment was achieved through dual blockade of the Aδ and C classes of meningeal nociceptors. Combination therapy that inhibits meningeal C-fibers and prevents calcitonin gene‒receptor peptide from activating its receptors on Aδ-meningeal nociceptors may be more effective than a monotherapy in reducing migraine days per month in patients with chronic migraine.